2011
DOI: 10.2118/127986-pa
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Fracture Spacing and Sequencing in Horizontal-Well Fracturing

Abstract: Horizontal wells with multiple fractures are now commonly used in unconventional (low-permeability) gas reservoirs. The spacing between perforations and the number and orientation of transverse fractures all have a major impact on well production.The opening of propped fractures results in the redistribution of local Earth stresses. In this paper, the extent of stress reversal and reorientation has been calculated for fractured horizontal wells using a 3D numerical model of the stress interference induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 19 publications
1
73
0
1
Order By: Relevance
“…Here, S is the dimensionless crack separation, F is the normalized stress-intensity factor, and a and b are the Dundurs elastic mismatch parameters (Dundurs 1967;Schmauder and Meyer 1992).…”
Section: Governing Integral Equationmentioning
confidence: 99%
“…Here, S is the dimensionless crack separation, F is the normalized stress-intensity factor, and a and b are the Dundurs elastic mismatch parameters (Dundurs 1967;Schmauder and Meyer 1992).…”
Section: Governing Integral Equationmentioning
confidence: 99%
“…The influences of the fracture spacing, rock mechanical properties and in-situ stress ratio were studied. Roussel and Sharma [10] used the same method as that in the work of Nagel and Sanchez-Nagel [9], however, the influence of fracture barriers (cap rock and base rock) was further considered. In that paper, it was found that an alternate fracture sequence (1-3-2-4-5, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…An alternative fracture sequence (1-3-2, etc.) is recommended in Roussel et al [10]. With this sequence, the stress reorientation between the first und the third fracture is minimized as shown in Figure 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al (1995) and Weijers et al (1999) reported some field data and observations on hydraulic fracture reorientation of injection wells from field studies (mainly from Belridge and Lost Hills reservoirs). It is noted that if the distance between the multiple injection wells is small such that pronounced stress perturbations exists due to the large volume of injected fluid, the stress interference could influence the fracture geometry and orientation.. Over the years research has been conducted on predicting stress interference effect on hydraulic fracture reorientation (Wright et al 1995, Wright and Conant 1995, Weijers et al 1999, Philip et al 2005, Roussel and Sharma 2011. Recently, Bunger et al (2011) developed a coupled 2D displacement discontinuity method-based numerical simulator to predict parameters effecting the interaction among closely spaced hydraulic factures.…”
Section: Introductionmentioning
confidence: 99%